Content analysis of local magazines on the image of interior design - Fetalvo, Nestle Maris Carino; Buencamino Lorena M. (2009.)
This study aimed to determine if local magazines are projecting an image of interior design or of interior decoration. Objectives of the study include selecting of local magazines dealing with interior design (Real Living, My Home and Metro Home & Entertaining), identifying definitions and characteristics of interior design and of interior decoration, classification of titles and articles from the magazines according to the categories of interior design and of interior decoration. Following a qualitative study on content analysis of local magazines, key words and/or phrases are extracted from the titles of the magazine articles in the table of contents. These words were classified into the categories interior design and of interior decoration. Research samples are articles listed on the table of contents from each purposively selected magazine. Whether analyzed individually or consolidated, these magazines project an image of the Interior Design profession as Interior Decoration itself. Therefore, these magazines are largely projecting an image of interior decoration over Interior Design. There is a need for further studies on why these magazines project this image and another for a study parallel to the thesis of Ubana (2008), but using magazines. Moreover, the researcher recommends on updating how wide in our social strata that interior design is accepted and lastly, a development of a mechanism by which the public can be aided in differentiating interior design from interior decoration through print media.
Thesis (BS Interior Design)--University of the Philippines Diliman
Keywords: Interior decoration -- Philippines